Botulinum toxin and Dentistry: integrative review (Research, Society and Development, 2022)
Introduction: Botulinum toxin has an important therapeutic application. Produced by the bacterium Clostridium botulinum, it gained great prominence in the dental sector for having safe, fast and effective protocols. Objectives: To compile and synthesize updated information about the use of botulinum toxin in dentistry. Methodology: This is na integrative literature review. For data collection, searches were performed on PubMed, Scientific Electronic Library Online and Virtual Health Library platforms by consulting the descriptors: “Botulinum Toxins, Type A”, “Dental Care” and “Esthetics”. Complete studies in English, Portuguese and Spanish published in the period from 2012 to 2022 were selected. Results: 55 articles stood out, whose analysis allowed us to identify that the drug is effective as an alternative treatment in aesthetic and functional/pathological cases. As examples, we can mention the correction of facial asymmetries, combat and attenuation of various types of wrinkles and treatment of tension headache, temporomandibular disorder, bruxism, masseter hypertrophy and trigeminal neuralgia. Conclusion: The effects of botulinum toxin application are not definitives. Therefore, its administration causes temporary chemical denervation. The success of the technique mainly depends on the correct identification of the muscle(s) involved in the problem, on the absence of general muscle hyperactivity in the area of administration and on possible iatrogenic causes. Thus, the toxin proves to be effective in cases where the current protocols and the limitations of the chosen therapy are respected.